KORELASI ANTARA SISTEM MANAJEMEN MUTU ISO 9001:2015 DENGAN SISTEM MANAJEMEN PENDIDIKAN ISO 21001:2018 - Wiwiet Prihatmadji; Ali Zulfikar; Susi Oktafiani; Aris Hendrawan; Fera Lufhidarani Pranita (POLITEKNIK LP3I JAKARTA, 2022)
Quality Management System (QMS) ISO 9001:2015 and Education Organization Management System (SMOP) ISO 21001:2015 are management systems that emphasizes the closeness of processes through the application of the PDCA Cycle, Risk-Based Thinking Framework and in harmony with other ISO management systems. The process approach involves a systematic interaction between management processes, so as to achieve the desired results in accordance with the policies, objectives and strategies of the organization's plans. The ISO 21001 and ISO 9001 management systems are designed, implemented and improved based on the PDCA (Plan-Do-Check-Action) model and translated by SN DIKTI as the Quality Cycle of Penetapan, Pelaksanaan, Evaluasi, Pengendalian dan Peningkatan (PPEPP). This cycle results in Continuous Quality Improvement (CQI). Risk AwarenessÂ creates a basis for increasing the effectiveness of the education management system, in order to achieve good results and prevent negative effects.Keywords: ISO 9001:2015, ISO 21001:2018, Process Approach, PDCA, Risk Awareness